Situating knowledges, making kin and telling stories: geographical encounters with Donna J Haraway - Greenhough, B (Elsevier, 2024)
Donna Haraway has been a constant presence in geographical thought and practice over the past 30 years. From her early and very influential essay on Situated Knowledges, to her more recent engagements with the Anthropocene in Staying with the Trouble, her work has become a key reference point for questioning the production of geographical knowledge. In this commentary I trace the influence of Haraway's thought on geographical scholarship, exploring how it both shapes our disciplinary histories and provides a critical lens upon them. In particular I highlight how Haraway's work informs feminist and more-than-human geographies, resonates with Indigenous ontologies and challenges geographers to reflect critically on the implications of their positionality and provinciality for academic research.